Integrated analysis of immune parameters, miRNA-mRNA interaction, and immune genes expression in the liver of rainbow trout following infectious hematopoietic necrosis virus infection - Wu, Shenji; Huang, Jinqiang; Li, Yongjuan; Lei, Mingquan; Zhao, Lu; Liu, Zhe (Frontiers in Immunology, 2022)
Rainbow trout (Oncorhynchus mykiss) is an important economical cold-water fish worldwide. However, infection with infectious hematopoietic necrosis virus (IHNV) has severely restricted the development of aquaculture and caused huge economic losses. Currently, little is known about the immune defense mechanisms of rainbow trout against IHNV. In this study, we detected the changes of immune parameters over different post-infection periods (6-, 12-, 24-, 48-, 72-, 96-, 120-, and 144 hours post-infection (hpi)), mRNA and miRNA expression profiles under 48 hpi (T48L) compared to control (C48L), and key immune-related genes expression patterns in rainbow trout liver following IHNV challenge through biochemical methods, RNA-seq, and qRT-PCR, and the function of miR-330-y was verified by overexpression and silencing in vitro and in vivo. The results revealed that alkaline phosphatase (AKP), alanine aminotransferase (ALT), catalase (CAT), and total superoxide dismutase (T-SOD) activities, and lysozyme (LZM) content showed significant peaks at 48 hpi, whereas malondialdehyde (MDA) content and aspartate aminotransferase (AST) activity decreased continuously during infection, and acid phosphatase (ACP) activity varied slightly. From RNA-seq, a total of 6844 genes and 86 miRNAs were differentially expressed, and numerous immune-related differentially expressed genes (DEGs) involved in RIG-I-like receptor signaling pathway, Toll-like receptor signaling pathway, NOD-like receptor signaling pathway, cytokine-cytokine receptor interaction, and antigen processing and presentation were significantly upregulated in T48Lm group, including IFIH1, DHX58, MAVS, TRAF3, IRF3, IRF7, MX1, TLR3, TLR8, MYD88, NOD1, NOD2, IL-8, CXCR1, CD209, CD83, and TAP1. Integrated analysis identified seven miRNAs (miR-425-x, miR-185-x, miR-338-x, miR-330-y, miR-361-x, miR-505-y, and miR-191-x) that target at least three key immune-related DEGs. Expression analysis showed that IFIH1, DHX58, IRF3, IRF7, MX1, TLR3, TLR8, and MYD88 showed a marked increase after 24 hpi during infection. Further research confirmed TAP1 as one of the targets of miR-330-y, overexpression of miR-330-y with mimics or agomir significantly reduced the expression levels of TAP1, IRF3, and IFN, and the opposite effects were obtained by inhibitor. These results facilitate in-depth understanding of the immune mechanisms in rainbow trout against IHNV.